Incidental Prostate Carcinoma Diagnosed at Radical Cystoprostatectomy for Bladder Carcinoma: A Case Report - Paul, Sonal; Padmanabhan, Anitha; Gadgil, Nitin M (Annals of Pathology and Laboratory Medicine, 2020)
Introduction: The incidence of concomitant urothelial carcinoma of the bladder and adenocarcinoma of the prostate varies from 17% to 70% as per various literature studies. Case report: We report the case of 82 year old male who presented with hematuria and lower urinary tract symptoms. A cystoscopy was performed which was suggestive of a 6x4x5cm mass arising from the left anterolateral wall and dome of the bladder. A Transurethral biopsy of the bladder mass showed a high grade papillary urothelial carcinoma invading the muscularis propria. Following this, the patient underwent a radical cystoprostatectomy. Histopathological examination of the bladder mass confirmed High -grade urothelial carcinoma. The entire prostate was sampled which revealed Adenocarcinoma prostate, Gleason score 3+4=7, tumor volume 6cc. Conclusion: The incidence of incidentally detected prostatic adenocarcinoma in Carcinoma bladder cases is extremely variable. Complete sampling of the prostate helps in detecting these lesions.